The Bizarre World of Nontransitive Dice: Games for Two or More Players. (1st January 2017) - Grime, James
Summary: With nontransitive dice, you can always pick a dice with a better chance of winning than your opponent. There are well-known sets of three or sets of four nontransitive dice. Here, we explore designing a set of nontransitive dice that allows the player to beat two opponents at the same time. Three-player games have been designed before using seven dice. We introduce an improved three-player game using five dice, exploiting a reversing property of some nontransitive dice.